Cavernous hemangioma of left nasal meatus - Thimmaiah, Anil Hanakere; Gangaraj, Smitha Soubhagya; Paul, Thara Rachel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Hemangiomas are benign accumulations of blood vessels which occur in any tissue that includes vascular components like skin, mucosa, muscles, glands and bones. Hemangiomas arising in the nose are rare and account for less than 20% of all benign tumors of nose. They usually arise from inferior turbinate, middle turbinate and vomer. We present a case of cavernous hemangioma of left nasal cavity arising from mucosa of left middle meatus mimicking an antrochoanal polyp. Hemangiomas arising from middle meatus are extremely rare and to our knowledge this is the second case reported in literature.